2005
DOI: 10.1111/j.1365-2591.2005.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of substances leached or dissolved from pulp capping materials

Abstract: Substances dissolved from the adhesive system tested were cytotoxic for human dental pulp fibroblasts in culture, whilst substances leached from calcium hydroxide were biocompatible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 14 publications
1
63
3
2
Order By: Relevance
“…21 Moreover, it has been previously shown that Single Bond is cytotoxic to human dental pulp fibroblasts. 22 In a recent study, this material also induced angiogenic growth factors. 23 Thus, these results indicate a non-beneficial effect of adhesive systems used as pulp capping materials, at least in proximity to the dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, it has been previously shown that Single Bond is cytotoxic to human dental pulp fibroblasts. 22 In a recent study, this material also induced angiogenic growth factors. 23 Thus, these results indicate a non-beneficial effect of adhesive systems used as pulp capping materials, at least in proximity to the dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium conditioned by the bleaching agent was obtained as described by Cavalcanti et al 26 For obtaining the conditioned medium, 0.2 g of 35% H 2 O 2 (Ultradent, South Jordan, UT, USA) per 1 mL of culture medium was used. The conditioning time was 30 minutes, and immediately after conditioning the conditioned medium diluted to 10 …”
Section: Conditioned Mediummentioning
confidence: 99%
“…The release of unreacted monomers from resin composites may stimulate the growth of bacteria [18] and promote allergic or cytotoxic reactions to intraoral tissues [18]. Diffusion of water into resin matrices may result in the deterioration of the physical/ mechanical properties, decreasing the life expectancy of the interfaces by hydrolysis and microcrack formation [19,20]. Water ingress may, however, have related beneficial effects [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion of water into resin matrices may result in the deterioration of the physical/ mechanical properties, decreasing the life expectancy of the interfaces by hydrolysis and microcrack formation [19,20]. Water ingress may, however, have related beneficial effects [19,20].…”
Section: Discussionmentioning
confidence: 99%